1994
DOI: 10.1111/j.1745-6584.1994.tb00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mathematical Modeling of Diesel Fuel Liquid and Vapor Movement in Porous Media

Abstract: Two‐dimensional physical modeling of diesel fuel leaks was conducted in sand tanks to determine liquid and vapor migration characteristics. Mathematical modeling provided estimation of vapor concentrations at discrete times and distances from the vapor source and was compared to the physical experiment. The mathematical gaseous diffusion model was analogous to the Theis equation for ground‐water flow, accounted for sorptive effects of the media, and was calibrated using measured concentrations from the sand ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…The corresponding experimental system was designed to eliminate moisture, temperature, and pressure gradients across the soil bed. Density-driven advection is negligible when the specific gravity of the contaminant-laden air relative to clean air is less than 1.2 [Johnson and Kreamer, 1994]. This condition was met for both the toluene and TCE experiments in this work.…”
Section: Transport Model Developmentmentioning
confidence: 86%
“…The corresponding experimental system was designed to eliminate moisture, temperature, and pressure gradients across the soil bed. Density-driven advection is negligible when the specific gravity of the contaminant-laden air relative to clean air is less than 1.2 [Johnson and Kreamer, 1994]. This condition was met for both the toluene and TCE experiments in this work.…”
Section: Transport Model Developmentmentioning
confidence: 86%
“…Th ey showed that density-driven advection is not negligible in the case of an air-compound mixture that has a density 1.15 times higher than that of uncontaminated soil air. Johnson and Kreamer (1994) emphasized that the density limit for notable density-driven advection Verti cal mass transfer of trichloroethylene (TCE) in a low water-saturated porous medium was studied in laboratory columns. A numerical transport model was used to interpret the measured vapor breakthrough curves, to determine apparent TCE diff usion coeffi cients, and to analyze the steady-state conditi ons of verti cal vapor mass transport.…”
Section: Industrializati On and Technological Development During The mentioning
confidence: 99%
“…They showed that density‐driven advection is not negligible in the case of an air–compound mixture that has a density 1.15 times higher than that of uncontaminated soil air. Johnson and Kreamer (1994) emphasized that the density limit for notable density‐driven advection is about 1.2. This ratio is 1.27 at 20°C for saturated TCE vapor and thus density‐driven advective mass transport might be significant for this compound.…”
mentioning
confidence: 99%
“…Dharmavaram et al (1994) evaluated the fate and transport processes in an ammonia spill from a barge. Johnson and Kreamer (1994) used sand tanks for physical modeling of diesel fuel leaks; liquid and vapor phase data were compared to mathematical models. Based on their results, monitor placement for underground diesel fuel storage systems can be improved.…”
Section: Site Assessmentmentioning
confidence: 99%